The Effectiveness of Using E-Modules Assisted by Animaker, Wordwall, and Heyzine Flipbook on the History of the Proclamation of Indonesian Independence in History Learning for Class XI of Darul Abror Vocational School - Wildan Rifai Anwar; Syaiful Amin (Historia, 2027)
This study aims to test the effectiveness of the use of E-Modules Assisted by Animaker, Wordwall, and Heyzine Flipbook Material on the History of the Proclamation of Indonesian Independence in History Learning for Class XI. This study is a type of Quantitative Experimental research with a One-Group Pretest-Posttest design that focuses on testing a product through the N-Gain test from the average results of Pretests and Posttests. The research process was carried out at SMK Darul Abror which has limited teaching media, especially History teaching media available for students. The objects of this study were all classes of Class XI of SMK Darul Abror, with the research subjects being class XI DKV 1, totaling 31 people. The results of the study showed a high level of effectiveness of the use of E-Modules in History Learning for Class XI. This is indicated by a large change in the average value of the Pretest of 38.5 to 88.5 in the average value of the Posttest results. The results of the N-Gain test in this study reached a value of 0.81 which is included in the high category or very effective for effectiveness in the learning process.